Curriculum Management in Improving Education Quality (Descriptive Study of MA Zainul Bahar Wringin Bondowoso) - Lucky Damara Yusuf (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Education management implements management principles in managing educational practices to be effective and efficient so that organizations in education produce quality output. hinder and support the implementation of the curriculum in improving the quality of education at MA Zainul Bahar Wringin Bondowoso. In creating a better, innovative, and productive generation, it is necessary to have educational components that are planned in a systematic and orderly manner. Educational components both in terms of institutions, curriculum, facilities, media, education officers and funds must be considered in the presence of good and structured management. Education is said to be of quality is an education that can produce graduates who have potential and competence. Both academic competencies or special competencies, which are based on personal and social competencies, which are collectively referred to as life skills. Life skills education is quality education, both quality in fact and quality in perception.